ARTISTIC-PHILOSOPHICAL INTERPRETATIONS OF THE DUTY AND RESPONSIBILITY (Scientific journal of the Fergana State University, 2023)
The article analyzes the views of the great poet and thinker Alisher Navoi on upbringing of children, the duties and responsibilities of parents in this regard.